2018
DOI: 10.1063/1.4990038
|View full text |Cite
|
Sign up to set email alerts
|

Complex contagions with timers

Abstract: There has been a great deal of effort to try to model social influence-including the spread of behavior, norms, and ideas-on networks. Most models of social influence tend to assume that individuals react to changes in the states of their neighbors without any time delay, but this is often not true in social contexts, where (for various reasons) different agents can have different response times. To examine such situations, we introduce the idea of a timer into threshold models of social influence. The presenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Because all binary models, mentioned above, have been extensively investigated for years, many modifications and extensions of their original formulations have been proposed; a short review on modifications of the majorityvote model can be found in [29], on the Watts threshold model in [30], on the q-voter model in [31] and on the Galam model comprehensive review has been written by the author of the model [32,33]. Among many extensions, going into different directions, the introduction of an additional type of the social response was particularly interesting from the point of view of social/psychological sciences, as well as the theory of non-equilibrium phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Because all binary models, mentioned above, have been extensively investigated for years, many modifications and extensions of their original formulations have been proposed; a short review on modifications of the majorityvote model can be found in [29], on the Watts threshold model in [30], on the q-voter model in [31] and on the Galam model comprehensive review has been written by the author of the model [32,33]. Among many extensions, going into different directions, the introduction of an additional type of the social response was particularly interesting from the point of view of social/psychological sciences, as well as the theory of non-equilibrium phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic trees analyzed in this paper, along with their associated pathways of contagion, have been studied previously in diverse disciplines. They have been called adoption paths [20], dissemination trees [40,41], spreading patterns [42], causal trees of disease transmission [43], diffusion structure patterns [44], the structure of diffusion events [45], and epidemic trees [46]. We have chosen to adopt the term "epidemic trees," although it comes with a significant caveat: Generally, the graph of the propagation paths for a contagion need not be a directed tree; in the case of a complex contagion [47], where each child node has two or more parents, the graph could be a directed graph with no cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the presence of a single hipster node increases the expected fraction of nodes who adopt product B at steady state from 0 nodes to half of the nodes. The main idea is that early adopters can influence later adopters in a way that depends on the adoption paths that are available [40]. Moreover, although the expected fraction of product-B adopters is 1/2, a realization will be equally likely to result in any number of product-B adopters, because every node is equally likely to be the hipster.…”
Section: Major Impact Of Few Individuals: Approximation On K-regumentioning
confidence: 99%
“…For a spreading process on a network, one can construct a dissemination tree, which describes how a contagion spreads through the network [40]. For a k-regular tree with only vulnerable nodes, the dissemination tree is the same k-regular tree, except that all edges are directed from the center towards the periphery.…”
Section: Major Impact Of Few Individuals: Approximation On K-regumentioning
confidence: 99%
See 1 more Smart Citation